the Fertilitas Perempuan: Analisis Durasi Sekolah dan Perempuan Sebagai Kepala Keluarga: Fertilitas Perempuan: Analisis Durasi Sekolah dan Perempuan Sebagai Kepala Keluarga - Kurniawan, Heru; Ramsito, Ramsito; Deyanti, Deyanti (Komunitas Manajemen Kompetitif, 2026)
The birth rate (fertility) is one of the demographic indicators that determine long-term national development. A low birth rate has negative effects, ranging from a decline in the productive workforce, an increase in the burden of healthcare, and economic slowdown. The purpose of this study is to examine how the duration of education and the condition of women as heads of households affect fertility. This study uses the Ordinary Least Squares (OLS) analysis method, with data collected from the Central Statistics Agency (BPS) over a 13-year period, from 2013 to 2023. The results of the study show that the length of education and women as heads of households lead to a decline in birth rates. The length of education has a greater influence than women as heads of households. Policies such as providing compensation for women with families who continue their education, providing childcare for working heads of households, and paid maternity leave for female heads of households with husbands are needed.